Entrance, Darabshaw House - Ghosh, Ayan (2023)
The entrance to Darabshaw House is through a semi-circular arched doorway with moldings. Above the entrance, a row of stone brackets supports a balcony that runs around the cornice. Note the bollard on the footpath. Originally, bollards were used for mooring ships to the dock but are now installed to control road traffic.